JAMINAN HAK HIDUP BAGI PENGUNGSI ROHINGYA DALAM PERSPEKTIF HUKUM INTERNASIONAL - Maulana Iqbal (2023)
Refugees are a fairly complex problem in Indonesia. Apart from not ratifying the 1951 UNHCR Convention by Indonesia, the rise of refugees from various countries has become a separate problem for Indonesia, so that Indonesia is a temporary residence or only a transit country for them. Refugees from the Rohingya ethnicity are one of the many refugees who come to Indonesia. The Rohingya ethnic group comes from the country of Myanmar, the poor treatment of this ethnic group by the state forces the Rohingya to move from one country to another as refugees. However, the unfavorable actions that befell these ethnic groups do not only occur in their home countries but also in countries where they are looking for a new place to live. The lack of guarantees for the life of the Rohingya makes the author want to make explicit research on guaranteeing humanity for the ethnic group in International Law. Therefore, this research is important because it discusses the guarantee of life for the Rohingya ethnicity which has been regulated in international law. This study uses a normative juridical research method that examines legal provisions relating to the object of research from the facts that have occurred. This research is deductive in nature by providing a researcher's perspective in looking at the guarantee of life for the Rohingya ethnicity and the role of Indonesia which can now have a major role in overcoming this problem. The sources obtained in this study have been analyzed to see future good actions in providing a better life and humanitarian protection for the Rohingya ethnicity.